Human-centered design and early evaluation of an interface for mobile-manipulator-mediated pediatric occupational therapy - Morales Mayoral, Rafael; Logan, Samuel W.; Fitter, Naomi T. (Frontiers in Robotics and AI, 2025)
Assistive mobile robots can play an important role in supporting individuals with disabilities. While the field of robot control interfaces for individuals with disabilities is growing, there is little work done on such systems for children end users specifically. Accordingly, we pursued the design of an adapted robot control interface for use in child pediatric occupational therapy (OT). Our target end user, a nine-year-old child with cerebral palsy, leveraged the interface to perform instrumental activities of daily living (e.g., play) with a modern mobile manipulator. We used an iterative design process to adjust and improve the interface via input from the participant’s caregivers and occupational therapist, as well as objective participant performance data. Furthermore, we tested the participant’s ability to utilize our interface by creating two testing cases: a control case (in which our participant performed standard ALD/IADL tasks) and an experimental case (in which our participant performed ADL/IADL practice activities more tailored toward the child). Key insights during the process included the need for sensitivity to taking up space on the child user’s existing power wheelchair, the advantages of integrating technologies familiar to the child (e.g., gaming controls, iPads) in our system design, and the potential value of integrating playful mischief (including playful interactions between the child, their caregivers, and their clinicians) as a part of the playbook for pediatric OT. This work can serve to inform and augment new OT strategies for the marginalized population of young children with disabilities.